CURRENT RATIO, DEBT TO EQUITY RATIO DAN TOTAL ASSET TURNOVER PENGARUHNYA TERHADAP RETURN ON ASSETS - RIZMA DHARMAYANTI; FRIYANTO - (STIE Indonesia Malang, 2021)
The study aims to determine and analyze whether the Current Ratio, Debt to Equity Ratio, and Total Asset Turnover have an effect on Return On Assets in the infrastructure sector companies listed on the Indonesia Stock Exchange in 2017-2019. The analytical method used in this research is the multiple linear regression method. The research method used is a quantitative method with a descriptive research approach. The type of data used in this study is secondary data, the data collection technique used is non-participant observation technique. And in this study, the sampling method used is the Purposive Sampling Method. From 57 companies, a sample of 27 companies was taken. The results of this study indicate that partially, the Current Ratio variable has no significant effect on Return On Assets, while the Debt to Equity Ratio and Total Asset Turnover variables have a significant effect on Return On Assets. And simultaneously, the variables Current Ratio, Debt to Equity Ratio and Total Asset Turnover have a significant effect on Return On Assets in infrastructure sector companies listed on the Indonesia Stock Exchange in 2017-2019.Keywords: Current Ratio, Debt to Equity Ratio, Total Asset Turnover, Return On Assets.